2018
DOI: 10.1097/sap.0000000000001291
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Utility of the Drainless Abdominoplasty in the Post–Bariatric Surgery Patient

Abstract: Despite post-bariatric surgery patients being considered higher risk for postoperative complications, drainless abdominoplasty can be safely offered to this population by using a progressive tension suture technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
1
0
4
Order By: Relevance
“…3,4,17 Some surgeons even go so far as to completely dispense the simultaneous use of drainage when using PTS. [18][19][20] Nevertheless, when PTS is used in combination with drainage, it can reduce the risk of seroma complications, drain volume, and time to drain removal. Khan et al 21 reported that in 2 groups of abdominoplasty, they could lower mean time for drain removal from 11.9 + 7.9 days in the non-PTS group to 9.2 + 4.3 days in the PTS group.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,17 Some surgeons even go so far as to completely dispense the simultaneous use of drainage when using PTS. [18][19][20] Nevertheless, when PTS is used in combination with drainage, it can reduce the risk of seroma complications, drain volume, and time to drain removal. Khan et al 21 reported that in 2 groups of abdominoplasty, they could lower mean time for drain removal from 11.9 + 7.9 days in the non-PTS group to 9.2 + 4.3 days in the PTS group.…”
Section: Discussionmentioning
confidence: 99%
“…als auch ohne Verknüpfungsnähte (engl. Progressive Tension oder Quilting Sutures) zwischen dem oberflächlichen und tiefen Fasziensystem, bereits als unbedenklich hinsichtlich der Patientensicherheit ein [2,3,7]. Während die gegenwärtige Datenlage die routinemäßige Anwendung von Drainagen nicht rechtfertigt, existieren in zunehmender Zahl Studienresultate, die für einen Verzicht auf Wunddrainagen sprechen [5].…”
Section: Diskussionunclassified
“…Drainagen gehen hingegen nachweislich mit einem eingeschränkten Patientenkomfort und einem Infektionsrisiko ausgehend von der Punktionsstelle einher [3,6]. In der aktuellen Fachliteratur finden sich Hinweise auf nur geringe Komplikationsraten bei Straffungseingriffen ohne Drainagen [2,3,7]. Dennoch ist der Einsatz von Wunddrainagen bei plastischchirurgischen Eingriffen national und international weit verbreitet [4,[8][9][10] Die Studienteilnehmer wurden prospektiv in zwei Gruppen mit Drainagen (MD) und ohne Drainagen (OD) randomisiert.…”
Section: Introductionunclassified
See 2 more Smart Citations